2011
DOI: 10.5152/tjh.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Are cup-like blasts specific to AML patients with FLT3 ITD and a normal karyotype? An ALL case report and review of the literature

Abstract: Cup-like morphology is defined as cup-like nuclear invagination spanning ≥25% of the nuclear diameter in >10% of blasts. Studies have shown that FLT3 ITD and normal cytology are strongly associated with cup-like morphology in acute myeloid leukemia (AML) patients. Herein we describe a patient with cup-like blasts that was diagnosed and treated for common acute lymphoblastic leukemia (ALL). In contrast to the literature, the presented case was Philadelphia chromosome positive and FLT3 ITD negative. (Turk J Hema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Flow cytometry immunophenotyping and/or immunohistochemical studies showed expression of CD19, CD10, CD22, TdT, and CD34, without myeloid or T-cell lineage markers [7,8]. Complete remission after induction was achieved in both cases [7,8]. One similar case was reported in a 7-year-old girl and was associated with normal karyotype and IKZF1 deletion [9].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Flow cytometry immunophenotyping and/or immunohistochemical studies showed expression of CD19, CD10, CD22, TdT, and CD34, without myeloid or T-cell lineage markers [7,8]. Complete remission after induction was achieved in both cases [7,8]. One similar case was reported in a 7-year-old girl and was associated with normal karyotype and IKZF1 deletion [9].…”
mentioning
confidence: 84%
“…was finally diagnosed in the first case [7], while the second showed B-ALL with near-triploid karyotype and TP53 and DNMT3A mutations [8]. Flow cytometry immunophenotyping and/or immunohistochemical studies showed expression of CD19, CD10, CD22, TdT, and CD34, without myeloid or T-cell lineage markers [7,8].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Cup-like nuclear morphology is defined by the presence of 10% or more blasts with at least one prominent nuclear invagination (or 'cup') spanning at least 25% of the nuclear diameter [2]. Except for one case of ALL in which 20% of the blasts showed cupping [3], this feature appears to have been described only in AML, generally nucleophosmin1-mutated [4]. The finding of numerous cupped blasts, particularly as seen in our first case with 80% cupped blasts ( Figure 1) therefore, strongly suggested a diagnosis of AML, which unexpectedly turned out to be not AML, but MLL-rearranged B-cell precursor ALL.…”
Section: Nuclear Cupping In the Blasts-more To The Cup Than Myeloidmentioning
confidence: 99%
“…The cuplike nuclei have a central pallor that is clefted, indented, folded, or "fishmouthed," with loose chromatin and 1 to 3 nucleoli. Mehtap et al, 2 Kussick et al, 3 and Bennett et al 4 described cuplike nuclei as having a nuclear invagination spanning 25% or greater of the nuclear diameter and in more than 10% of the blasts. Immunophenotypically, this unusual variant is similar to the microgranular variant of acute promyelocytic leukemia (APL).…”
mentioning
confidence: 99%